Maintenance of smoking cessation in Korean single mothers - Mi-Ji Lee; Kang-Sook Lee (BMC, 2021)
Abstract Background Single mothers in South Korea are vulnerable to developing smoking habits, due to many difficulties and limitations; however, they have often been overlooked by smoking cessation support services. Therefore, this study aimed to investigate the general and smoking-related characteristics of single mothers registered with the Visiting a Smoking Cessation Service in Seoul, South Korea, to identify factors associated with smoking cessation maintenance at 4 weeks and 24 weeks after they initially quit smoking. Methods The participants were 77 single mothers registered in the Smoking Cessation Service Program. Data were included from a three-year span (January 2017-December 2019). Smoking cessation counseling, motivational enhancement, and self-exploration counseling were provided for six months. The participants were evaluated on their smoking cessation status at 4 weeks and 24 weeks. Results Most participants were aged 22 years or younger. The rates of smoking cessation maintenance were 58.4 and 18% at 4 weeks and 24 weeks, respectively. The higher the number of counseling sessions, the higher the participants' chances of maintaining smoking in all non-smoking periods, and whether pregnancy, CO level, and drinking were significant only in a short-term non-smoking period (4 weeks). Conclusions Our results suggest that the number of smoking cessation counseling sessions is important for long-term smoking cessation beyond short-term cessation in single mothers. To increase the smoking cessation rate of single mothers, it is important to conduct customized smoking cessation counseling at the time of smoking cessation and continue such counseling in the long term.